Hölderlin und das Wesen der Dichtung - Heidegger, Martin 1889-1976 (Munich Verlag Albert Langen-Georg Müller, 1937)
It was no coincidence that Martin Heidegger chose Friedrich Hölderlin for his redefinition. Alongside Heinrich von Kleist, it was Hölderlin in particular who emphasised the need to abolish the genre differences between philosophy and literature or thinking and poetry. His late hymns in particular are poetic philosophy that tentatively poses new questions that were traditionally reserved for philosophy. So when Hölderlin wrote "Was aber bleibet stiften die Dichter", this was his poetic answer to the question of the nature of philosophy.Martin Heidegger's reading of Hölderlin's poetry was therefore able to refer to Hölderlin himself if it proceeded philosophically. With this certainty, Heidegger then also uncovered content that he himself could not gain from his study of Plato, for example. Holger Schmied's (Tübingen) subtle reflections on the "Greek sphere" of the two protagonists opened up new horizons for the understanding of Heidegger's interpretation of Plato. Plato appeared to have been appropriated via Hölderlin, virtually snatched back from poetry. The counter-orientation with which Heidegger understood how to read classical texts became very clear.By always insisting on the philosophical core of Hölderlin's poetry, Heidegger was also able to overcome difficulties in overcoming other positions.His lifelong debate with Immanuel Kant, for example, was conducted under the title of the "twisting" of subjectivity.However, as Stephanie Bohlen from Freiburg has precisely described, it was only through his study of Hölderlin that he saw a mental and conceptual ability to free himself from the idea of man as subject.Over time, Heidegger's "dialogue" (Stephanie Bohlen) with Hölderlin increasingly took the form of an alignment.Thought and poetry became more like siblings, illuminating each other's spheres of knowledge. Heidegger's criticism of technology, for example, is entirely motivated by Hölderlin. He heard the accusation that man was confronting nature like a policeman confronts a thief with the same concern as Hölderlin's fear of the escape of the gods. Both saw the threat to the world coming from a false understanding of nature. Source: http://www.berliner-zeitung.de/16141150 ©2017 (Translated with DeepL.com)
Keywords: Hölderlin, Friedrich -- 1770-1843; 19th Century (1801-1900); Poetry; Germany